Copper-catalyzed cross-coupling and sequential allene-mediated cyclization for the synthesis of 1, 2, 3-triazolo[1, 5-a]quinolines. Issue 36 (8th September 2020) - Yang, Jianhua; Xiong, Shaoqi; Ren, Yongsheng; Xiao, Tiebo; Jiang, Yubo
Abstract : In this paper, a tandem reaction involving copper-catalyzed cross-coupling and allene-mediated cyclization of 1-(2-ethynylaryl)-1, 4-disubstituted-1, 2, 3-triazole with N -tosylhydrazone has been developed. Abstract : In this paper, a tandem reaction involving copper-catalyzed cross-coupling and allene-mediated cyclization of 1-(2-ethynylaryl)-1, 4-disubstituted-1, 2, 3-triazole with N -tosylhydrazone has been developed. This method features operational simplicity, excellent functional group compatibility, broad substrate scope, and easily available feedstock, providing an efficient and practical strategy for the synthesis of highly functionalized 1, 2, 3-triazolo[1, 5- a ]quinolines.